DILEMA PEMANFAATAN RUMAH SUSUN SEDERHANA SEWA UJUNA PASCAGEMPA DI KOTA PALU SULAWESI TENGAH - Murni Ratna sari Alauddin; Nursamsir Nursamsir; Indar Ismail Jamaluddin (Journal Publicuho, 2021)
After the earthquake, tsunami, and liquefaction on 28 September 2018, the condition of the five-story building was damaged, but it is still inhabited by dozens of families. This paper seeks to explore the attitude of the Palu City Government-Regional People's Representative Council (DPRD), residents, and parties outside the government and outside the residents regarding the use of these flats after the earthquake. The research was conducted qualitatively. Primary data were collected from direct observation and interviews and sources of mass media coverage also complement the secondary data needs. Borrowing Robert K Merton's structural functionalism theory, this research finds a condition if after a disaster, residents strengthen their institutions by building consensus or mutual agreement. Meanwhile, the City Government of Palu, although stated that they prohibited them from returning to the apartment, they have not been able to provide a more feasible housing solution after the earthquake. Ironically, members of the DPRD, as partners of the mayor in the government in Palu City, do not yet know about this condition.